Neutrino flavour waves through the quantum vacuum: A theory of oscillations - Markku Oksanen; Nico Stirling; Anca Tureanu (Physics Letters B)
We propose a theory for neutrino oscillations, in which the flavour neutrinos are treated as waves of massless particles propagating in a “refractive quantum vacuum” and obeying a relativistically covariant equation of motion. The difference in strength between weak interactions and mass-generating interactions is argued to allow for the production and detection of flavour neutrinos in weak interactions as massless particles. They experience the mass-generating interactions as coherent forward scattering in the Brout–Englert–Higgs vacuum, which induces macroscopically multi-refringent effects. The flavour neutrino wave is then found to have a universal effective refractive mass in vacuum and a unique group velocity for a given energy. The coherence of the wave is manifest throughout and, at every moment of the propagation, the energy of the waves is the same. The standard oscillation probability in vacuum is obtained and the effects of matter are incorporated in a natural way.